Randomised controlled trial of Helicobacter pylori testing and endoscopy for dyspepsia in primary care. Issue 7291 (14th April 2001) - Delaney, B C; Wilson, S; Roalfe, A; Roberts, L; Redman, V; Wearn, A; Hobbs, F D R
Abstract: Objective: To determine the cost effectiveness of a strategy of near patient Helicobacter pylori testing and endoscopy for managing dyspepsia. Design: Randomised controlled trial. Setting: 31 UK primary care centres. Participants: 478 patients under 50 years old presenting with dyspepsia of longer than four weeks duration. Interventions: Near patient testing for H pylori and open access endoscopy for patients with positive results. Control patients received acid suppressing drugs or specialist referral at general practitioner's discretion. Main outcome measures: Cost effectiveness based on improvement in symptoms and use of resources at 12 months; quality of life. Results: 40% of the study group tested positive for H pylori . 45% of study patients had endoscopy compared with 25% of controls. More peptic ulcers were diagnosed in the study group (7.4% v 2.1%, P=0.011). Paired comparison of symptom scores and quality of life showed that all patients improved over time with no difference between study and control groups. No significant differences were observed in rates of prescribing, consultation, or referral. Costs were higher in the study group (£367.85 v £253.16 per patient). Conclusions: The test and endoscopy strategy increases endoscopy rates over usual practice in primary care. The additional cost is not offset by benefits in symptom relief or quality of life.